Effectiveness of Knowledge Economy Determinants: Case of Selected EU Members - Prokop, Viktor; Stejskal, Jan (Academic Conferences and Publishing International, 2017)
Nowadays, economic actors more frequently force to seek new sources of competitive advantage – usually knowledge, to help to build the competitive advantage and sufficiently set them apart from the competition. Therefore, we can see a shift from traditional resources, such as work, land, and capital towards knowledge and its use, especially from hard factors (e.g., infrastructure) towards soft (intangible) factors such as local atmosphere, synergetic effects, human capital, and knowledge assets. However, most countries fail in their attempt to become knowledge or knowledge-based economies and they are not effective during the processes of knowledge creation, use, dissemination and commercialization. We can see a lack of studies analysing and comparing countries´ efficiency during this processes at EU 28 level. We fill this gap and evaluate the efficiency of these processes by using determinants of knowledge economy within EU 28 countries. These determinants are divided into four drivers (pillars) such as: (i) economic incentive and institutional regime, (ii) educated and qualified workers, (iii) an effective innovation system, and (iv) information infrastructure. For our analyses, we used Data Envelopment Analysis which is commonly used for evaluating the effectiveness and productivity of comparable production units based on the size of inputs and outputs. Results show that most of European countries are not effective in the processes of using determinants of knowledge economy (mainly financing of research and development). The main advantage of our research is that, the Data Envelopment Analysis provides practical implications (for each country) on how to improve and how to change inputs and outputs to become efficient. As a data source, we use data from Eurostat databases.
Efektivnost determinantů znalostní ekonomiky: případová studie vybraných zemí EU
Keywords: knowledge economy; competitiveness; determinants; EU members; effectiveness; innovation; public funding; znalostní ekonomika; konkurenceschopnost; determinanty; EU země; efektivnost; inovace; veřejné prostředky